Computer program in sign language for controlling mobile objects and communicating with people - Moldamurat, Khuralay; Tulembayeva, Aigul; Ryspaev, Askhat; Belgibekov, Niyaz; Peryakina, Lyudmila; Bakyt, Makhabbat (International Journal of Public Health Science (IJPHS), 2025)
This article emphasizes the need for effective communication methods for people with disabilities, focusing on gestures and finger movements. The study aims to address the communication support gap for this group by creating a specialized Kazakh IT dictionary. It explores practical ways to facilitate communication for people with disabilities through gestures, utilizing computer software for the IT dictionary. The article presents key variables, study design, and data analysis procedures. Results show computer programs effectively enable communication for individuals with disabilities. The study's novelty lies in the IT vocabulary covering gestures, benefiting pedagogy, education, and related fields. Computational linguistics, like automatic language processing and machine translation, enhances communication facilitation for the disabled. Practical recommendations are offered for implementing research findings, improving communication and overall quality of life for people with disabilities. In conclusion, the article stresses the importance of effective communication methods, especially gestures, for the disabled. The IT vocabulary creation through computational linguistics offers innovative ways to enhance communication accessibility, prompting further research.